Fiscal decentralisation and economic growth across states: new evidence from Malaysia - Abd Ghani, Judhiana; Muhamad Senan, Mohamad Khair Afham; Abdullahi, Asna Atqa; Mohd Noor, Norashidah (Universiti Putra Malaysia, 2021)
The link between fiscal decentralisation and state-level economic growth has often been overlooked, particularly in Malaysia, with its highly centralised federal fiscal system. Thus, using data from all 13 Malaysian states from 2006 to 2018, this study evaluated the degree of fiscal decentralisation and examined its effects on state economic growth. This study employed a new proxy for fiscal decentralisation (FD), a composite variable FD comprising two components: fiscal autonomy (FA) and fiscal importance (FI). The model was examined using the fixed effects technique with robust standard error panel analysis. The empirical results demonstrated that FI and FD were significant and positively impacted economic growth across states. The results also showed the significant and negative impact of budget balances resulting from persistent fiscal deficits on state economic growth, signalling states' heavy reliance on intergovernmental grants and borrowings (soft budget constraints). Thus, fiscal decentralisation has enabled the state governments to alleviate the soft budget constraint problem and reduce the negative impact of deficits on local economic growth. Overall, the results supported prior findings that fiscal decentralisation had a significant positive effect on state economic growth.